REVIEW OF HIGH-SPEED DIGITAL CMOS CIRCUITS - Elrabaa1, Muhammad E. S. (2020)
This paper presents a comprehensive review of the major state-of-the-art high-speed CMOS digital circuits. Focusing in particular on dynamic circuits such as conventional DOMINO, conditionalevaluation DOMINO and contention-free DOMINO. Also some high-performance non-dynamic (static) circuit techniques will be reviewed such as dual-threshold (DVT) circuits. The relative performance of these circuits in terms of speed, power, and noise margins is presented. Also the effects of technology scaling into the deep sub-micron regime on these techniques are evaluated and presented.